2012
DOI: 10.1007/s00213-012-2726-9
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposure to MDMA and amphetamine: sensitization, cross-sensitization, and response to dopamine D1- and D2-like agonists

Abstract: These data suggest that repeated MDMA exposure produces sensitization via a unique neurochemical effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 68 publications
5
37
1
Order By: Relevance
“…It is noteworthy that the failure to observe a concomitant increase in the number of forward locomotor counts contrasts with previously reported increases in forward locomotion, as measured by locomotor activity counts, that became sensitised following repeated intermittent exposure to ± MDMA (Ball et al, 2006;Lettfuss et al, 2013;Spanos and Yamamoto, 1989;Kalivas et al, 1998) including data from our laboratory (Bradbury et al, 2012). We previously reported that repeated daily injections of racemic MDMA (10.0 mg/kg, IP × 5 days) increased the number of ambulatory counts in response to 10.0 mg/kg MDMA and shifted the dose-effect curve for this response to the left when measured 2 days following the last experimenter-administered exposure to MDMA (Bradbury et al, 2012).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…It is noteworthy that the failure to observe a concomitant increase in the number of forward locomotor counts contrasts with previously reported increases in forward locomotion, as measured by locomotor activity counts, that became sensitised following repeated intermittent exposure to ± MDMA (Ball et al, 2006;Lettfuss et al, 2013;Spanos and Yamamoto, 1989;Kalivas et al, 1998) including data from our laboratory (Bradbury et al, 2012). We previously reported that repeated daily injections of racemic MDMA (10.0 mg/kg, IP × 5 days) increased the number of ambulatory counts in response to 10.0 mg/kg MDMA and shifted the dose-effect curve for this response to the left when measured 2 days following the last experimenter-administered exposure to MDMA (Bradbury et al, 2012).…”
Section: Discussioncontrasting
confidence: 82%
“…We previously reported that repeated daily injections of racemic MDMA (10.0 mg/kg, IP × 5 days) increased the number of ambulatory counts in response to 10.0 mg/kg MDMA and shifted the dose-effect curve for this response to the left when measured 2 days following the last experimenter-administered exposure to MDMA (Bradbury et al, 2012). The failure to replicate the increased number of horizontal ambulatory counts in the present data set might reflect the difference in preexposure and/or withdrawal period; MDMA was self-administered in the present study and the withdrawal period was 5 or 14 days.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Repeated administration of MDMA, gamma-hydroxybutyrate (GHB), and their combination results in long-lasting changes in hippocampal protein expression even after a washout period (van Nieuwenhuijzen et al, 2010), whereas MDMA treatment (0.2 and 2 mg/kg) twice a day for 6 days in young rats caused dose-dependent impairment in spatial learning and reduced LTP (AriasCavieres et al, 2010). Furthermore, just like AMPH, MDMA also produces sensitization after repeated exposure (Bradbury et al, 2012).…”
Section: Action Of Substituted Amphetamines and Cathinonesmentioning
confidence: 99%
“…MDMA, like other psychostimulant drugs of abuse, increased DA preferentially in the shell of the nucleus accumbens in rats (Cadoni et al, 2005) and this neurochemical effect became sensitized following repeated exposure (Kalivas et al, 1998). Acute exposure to MDMA produced hyperactivity that also became sensitized following repeated exposure (Bradbury et al, 2012, Schenk and Bradbury, 2015, Ball et al, 2009 even in 5-HT transporter knock-out rats (Lizarraga et al, 2014). The locomotor activating effects of MDMA have been shown to be dependent upon A C C E P T E D M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 98%